Strengthening the Shariah Governance Structure in Islamic Cooperative Sector - Nur Amni Mahmud Sabri; Supiah Salleh; Zurina Shafii; Mustafa Mohd Hanefah; Muhammad Iqmal Hisham Kamaruddin; Nurazalia Zakaria (Human Resource Management Academic Research Society, 2024)
Vol. 1 2 , No. 3